Sn02 Aerogels: Towards Performant and Stable PEFC Catalyst Supports. (14th September 2015) - Ozouf, Guillaume; Cognard, Gwenn; Maillard, Frederic; Guetaz, Laure; Heitzmann, Marie; Beauger, Christian
Abstract : Carbon free catalyst support were synthetized from tin dioxide aerogels obtained after supercritical CO2 drying of gels synthetized following an acid catalyzed sol-gel route, starting from metal alkoxides precursors. Sb doping at 10 at% was realized adding antimony alkoxide to the sol. The nanoscale morphology can be controlled during the sol-gel synthesis route and is retained after drying. The effect of doping with Sb (V) on the structure and the morphology of the material was investigated by XRD, SEM and nitrogen sorption. Our materials showed reasonable specific surface areas (85 m²/g). The bimodal narrow pore size distribution, centered on around 25 and 45 nm after calcination at 600 °C, is particularly well adapted to the foreseen application. Sb doped aerogel exhibited an impressive improvement of electronic conductivity, reaching 0.13 S/cm. This is representing a 4 orders of magnitude increase compared to pure SnO2 . This level of conductivity is almost equivalent to that of carbon Vulcan XC-72R measured in the same conditions (4 S/cm). These properties make SnO2 : Sb a very promising material as catalyst support for PEFC cathode. Three different methods of platinum deposition on SnO2 : Sb surface were studied. TEM and analysis was used to visualized Pt nanoparticles dispersion and sizes. Electrochemical features, like ECSA and ORR catalytic activities, of the best electrocalalysts in term of dispersion were investigated by the mean of RDE. Reduction by ethylene glycol method show higher mass catalytic activity than reference carbon-based electrocatlyst.